2016
DOI: 10.1038/srep20120
|View full text |Cite
|
Sign up to set email alerts
|

Altered rainfall patterns increase forb abundance and richness in native tallgrass prairie

Abstract: Models predict that precipitation variability will increase with climate change. We used a 15-year precipitation manipulation experiment to determine if altering the timing and amount of growing season rainfall will impact plant community structure in annually burned, native tallgrass prairie. The altered precipitation treatment maintained the same total growing season precipitation as the ambient precipitation treatment, but received a rainfall regime of fewer, larger rain events, and longer intervals between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 66 publications
4
34
0
Order By: Relevance
“…Furthermore, emergent responses, which occur subsequent to the first year of a multiyear rainfall period, have received little attention, in part because extended above-or below-average rainfall periods are expected to occur infrequently and are therefore impossible to observe a priori. Recent observations suggest that grassland responses to external forcings can change over multiple years as a result of legacies (Jones, Collins, Blair, Smith, & Knapp, 2016;Ratajczak et al, 2017), and comparing legacy and emergent components of ANPP in different grassland types can provide a more comprehensive understanding of how these processes influence ecosystem responses over periods of multiple years.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, emergent responses, which occur subsequent to the first year of a multiyear rainfall period, have received little attention, in part because extended above-or below-average rainfall periods are expected to occur infrequently and are therefore impossible to observe a priori. Recent observations suggest that grassland responses to external forcings can change over multiple years as a result of legacies (Jones, Collins, Blair, Smith, & Knapp, 2016;Ratajczak et al, 2017), and comparing legacy and emergent components of ANPP in different grassland types can provide a more comprehensive understanding of how these processes influence ecosystem responses over periods of multiple years.…”
Section: Introductionmentioning
confidence: 99%
“…Increased variability in rainfall can have large impacts on community composition and species diversity independent of rainfall amount (Knapp et al 2002). Jones et al (2016) conducted a 15-year precipitation variability grassland experiment and found that increased rainfall variability led to an increase in forb abundance and richness while dominant grasses remained relatively stable. Over time, rainfall variability led to the development of distinct communities as forb diversity increased, suggesting that rainfall variability plays a role in community assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Such time lags in the effects of precipitation on forbs are often overlooked, yet have recently been identified in other systems (Jones et al. , Dudney et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…F statistics and df are provided in Table 8. other functional groups, showed low resistance and high resilience, increasing after fire (Keeley et al 1981) and decreasing in dry years and in years following significant precipitation. Such time lags in the effects of precipitation on forbs are often overlooked, yet have recently been identified in other systems (Jones et al 2016, Dudney et al 2017. Non-native annual grasses fluctuated from year to year, responding positively to high rainfall, likely contributing to the negative correlation between native diversity and previous growing season precipitation.…”
Section: Discussionmentioning
confidence: 99%